Principle Ideas of Visible Thinking in Teaching English in Kazakhstan - Baigunissova, G. I.; Beisembayeva, Zh. A.; Abaidulla, M. Y. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
Visible thinking is a consistent, flexible and methodical approach to the organization of the educational process, allowing teachers to integrate the development of students’ thinking with the study of the materials. Currently, most foreign language teachers are unable to make full effective use of visual learning tools. For this reason, they often serve as decorations, rather than a tool for developing students’ language and thinking skills. As a result, this article examines key issues of using visual materials based on the principles of visible thinking in teaching English, proposed by experienced teachers from various backgrounds. Hence, a sociological survey was conducted among teachers in Kazakhstan, as well as interviews with teachers from Turkey and Kazakhstan. The survey offered questions that allowed delving into practical ideas and recommendations on the use of visible thinking in teaching English. The main results showed that images are the most effective material among other visual means in teaching English. Moreover, the article contains recommendations on how to integrate this approach in the English classroom under the principles of visible thinking.